Exponential decay for Kirchhoff wave equation with nonlocal condition in a noncylindrical domain - Ferreira, J.; Santos, M. L.; Matos, M. P.; Bastos, W. D. (Elsevier B.V., 2004)
In this paper, we prove the exponential decay as time goes to infinity of regular solutions of the problem for the Kirchhoff wave equation with nonlocal condition and weak dampingu(tt) - M (\\delU\\(2)(2)) Deltau + integral(0)(t) g(t - s)Deltau(.,s) ds + alphau(t) = 0, in (Q) over cap,where (Q) over cap is a noncylindrical domain of Rn+1 (n greater than or equal to 1) with the lateral boundary (&USigma;) over cap and alpha is a positive constant. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Kirchhoff wave equation; noncylindrical domain; exponential decay